2013
DOI: 10.3944/aott.2013.2928
|View full text |Cite
|
Sign up to set email alerts
|

Does platelet-rich plasma enhance microfracture treatment for chronic focal chondral defects? An in-vivo study performed in a rat model

Abstract: The addition of PRP application to microfracture treatment appears to enhance cartilage healing in chronic focal chondral defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Several trials have reported superior functional outcome and improved histologic scores when comparing PRPenhanced microfracture versus microfracture alone. 10,11 Data regarding outcomes of BioCartilage use in human subjects are limited to expert opinion, but controlled human trials examining outcome differences between standard microfracture and BioCartilage techniques are currently under way. To date, an overall beneficial effect has been observed in more than 1,000 patients implanted with BioCartilage, with no adverse events related to this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have reported superior functional outcome and improved histologic scores when comparing PRPenhanced microfracture versus microfracture alone. 10,11 Data regarding outcomes of BioCartilage use in human subjects are limited to expert opinion, but controlled human trials examining outcome differences between standard microfracture and BioCartilage techniques are currently under way. To date, an overall beneficial effect has been observed in more than 1,000 patients implanted with BioCartilage, with no adverse events related to this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To preserve the advantages of chondrocyte therapy in a single-stage approach to osteochondral defects, Marmotti and coworkers [ 123 ] offered a single-step therapeutic approach for osteochondral defects using autologous cartilage fragments loaded onto a scaffold composed of a hyaluronic acid derivative, human fibrin glue, and PRP, in a rabbit model. Finally, the same studies [ 124 , 125 ] using sheep and rats, evaluated the effect of PRP combined with microfractures on healing of chondral defects, showing that PRP application in addition to microfractures resulted in a better cartilage healing than microfractures alone.…”
Section: The Role Of Prp In the Regeneration Of Cartilagementioning
confidence: 99%
“…1,24,32,48 Preclinical in vivo studies are in line with these findings, reporting the beneficial role of PRP when applied after microfracture surgery. 14,29,30 Milano et al 30 reported that PRP had positive effects on cartilage repair and restoration after microfracture in chronic chondral defects in a sheep model, with better histological properties compared with controls, although the procedure was more effective when PRP was placed surgically on the defect as a fibrin glue gel in comparison with a liquid intra-articular injection. Milano et al 29 further investigated the postoperative injection approach by analyzing the effect of a multiple injection cycle; in this study on the treatment of knee focal chondral defect in sheep, 5 weekly injections of PRP after microfracture led to significantly better macroscopic, histological, and biomechanical results than the results in the control group treated with microfracture only.…”
Section: Discussionmentioning
confidence: 99%